Sproutel : how design roadmapping helped improve children's health & guide a growing company - Beckman, Sara, (SAGE Knowledge. Cases., 2018)
This case aims to introduce students to the "design roadmapping" process that connects customer and user experience design with product and technology roadmapping to create an integrated plan for future growth and development. Explicit consideration of customers in the roadmapping process places customers much more centrally in the strategic planning process than has traditionally been done. The setting for the case is a seven-year-old startup company, Sproutel, that began as a college project and whose success so far has come about in part due to the use of design roadmapping.